2020
DOI: 10.1002/cctc.202001268
|View full text |Cite
|
Sign up to set email alerts
|

Cross metathesis with acrylates: N‐heterocyclic carbene (NHC)‐ versus cyclic alkyl amino carbene (CAAC)‐based ruthenium catalysts, an unanticipated influence of the carbene type on efficiency and selectivity of the reaction

Abstract: Olefin metathesis has been widely explored as a handle for chemical diversification, a feature critical across chemical sectors. Cross metathesis (CM) with acrylic acid derivatives is an example of important but, due to the low catalyst's efficiency, industrially non‐utilized transformation. Here we report on systematic evaluation of ruthenium‐based catalysts bearing N‐heterocyclic carbene (NHC) or cyclic alkyl amino carbene (CAAC) ligands in cross metathesis with methyl acrylate. Dramatic influence of the car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 50 publications
0
10
0
1
Order By: Relevance
“…The N-DEP group is then too small to retard coupling, and 1-C1 Me decomposes nearly 10× faster than 1-C1 Ph . Consistent with this trend are the lower turnover numbers reported for C1 Me catalysts relative to their C1 Ph analogues in multiple contexts, ranging from ethenolysis to acrylonitrile metathesis. ,, …”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…The N-DEP group is then too small to retard coupling, and 1-C1 Me decomposes nearly 10× faster than 1-C1 Ph . Consistent with this trend are the lower turnover numbers reported for C1 Me catalysts relative to their C1 Ph analogues in multiple contexts, ranging from ethenolysis to acrylonitrile metathesis. ,, …”
Section: Resultsmentioning
confidence: 67%
“…Consistent with this trend are the lower turnover numbers reported for C1 Me catalysts relative to their C1 Ph analogues in multiple contexts, ranging from ethenolysis to acrylonitrile metathesis. 12 , 13 , 25 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[84] The comparative study of metathesis reactions catalyzed by cAAC and NHC stabilized ruthenium complexes by Kaczanowska et al shows that the efficiency and selectivity arehighly dependent on the types of carbenes. [85] It has also been shown that the cAAC stabilized ruthenium-based complexes can be employed in light-activated [86] and amine-assisted olefin metathesis. [87] cAAC stabilized lanthanoids have also been reported that show catalytic properties.…”
Section: Caac-stabilized Metal Complexes In Organic Catalysismentioning
confidence: 99%
“…Zusammenfassend haben wir versucht, den Leser davon zu überzeugen, dass EWG-aktivierte Ruthenium-Katalysatoren die Synthese verschiedener chemischer Verbindungen in vielen Bereichen der organischen und medizinischen Chemie ermçglicht haben und weiterhin ermçglichen werden. [147] Danksagung Wird anken dem "Catalysis for the Tw enty-First Century Chemical Industry"-Projekt, durchgeführt im Rahmen des TEAM-TECH-Programms der Stiftung der Polnischen Wissenschaft, mitfinanziert von der Europäischen Union aus dem Europäischen Fonds fürr egionale Entwicklung im Rahmen des Programms "Smart Growth". Ferner sind wir Dr. Cezary Samojłowicz und Herrn Krzysztof Skowerski fürh ilfreiche Diskussionen dankbar.…”
Section: Aufsätzeunclassified